2011
DOI: 10.1021/jf203213q
|View full text |Cite
|
Sign up to set email alerts
|

Tools for Studying Dry-Cured Ham Processing by Using Computed Tomography

Abstract: An accurate knowledge and optimization of dry-cured ham elaboration processes could help to reduce operating costs and maximize product quality. The development of nondestructive tools to characterize chemical parameters such as salt and water contents and a(w) during processing is of special interest. In this paper, predictive models for salt content (R(2) = 0.960 and RMSECV = 0.393), water content (R(2) = 0.912 and RMSECV = 1.751), and a(w) (R(2) = 0.906 and RMSECV = 0.008), which comprise the whole elaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
3
11
0
2
Order By: Relevance
“…NaCl content was also determined in ground pork samples and small samples of dry-cured hams by CT (Håseth et al, 2008). More recently, calibration models for NaCl content, moisture content and water activity in pork hams during the salting and the resting periods (Fulladosa, Santos-Garcés, Picouet, & Gou, 2010) and during the resting period (Santos-Garcés, Gou, Garcia-Gil, Santos-Garcés, Muñoz, Gou, Sala, & Fulladosa, 2012) were created using CT. At the same time, different articles (Arnau, 1998;Barat, Grau, Ibáñez, & Fito, 2005;Grau, Albarracin, Toldrá, Antequera, & Barat, 2008) have shown the interest of freezing the ham before salting, to have more homogeneous batch, easier to transport from production place to the transformer. Frozen/thawed hams have also shown a more rapid salt intake (Bañón, Cayuel, Granados, & Garrido, 1999;Barat et al, 2005;Barat, Grau, Pagán-Moreno, & Fito, 2004;Serra, Fulladosa, Gou, & Arnau, 2010;Sørheim & Berg, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…NaCl content was also determined in ground pork samples and small samples of dry-cured hams by CT (Håseth et al, 2008). More recently, calibration models for NaCl content, moisture content and water activity in pork hams during the salting and the resting periods (Fulladosa, Santos-Garcés, Picouet, & Gou, 2010) and during the resting period (Santos-Garcés, Gou, Garcia-Gil, Santos-Garcés, Muñoz, Gou, Sala, & Fulladosa, 2012) were created using CT. At the same time, different articles (Arnau, 1998;Barat, Grau, Ibáñez, & Fito, 2005;Grau, Albarracin, Toldrá, Antequera, & Barat, 2008) have shown the interest of freezing the ham before salting, to have more homogeneous batch, easier to transport from production place to the transformer. Frozen/thawed hams have also shown a more rapid salt intake (Bañón, Cayuel, Granados, & Garrido, 1999;Barat et al, 2005;Barat, Grau, Pagán-Moreno, & Fito, 2004;Serra, Fulladosa, Gou, & Arnau, 2010;Sørheim & Berg, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…When studying the reduction of sodium content in dry-cured hams, X-ray tomography is a useful tool for the continuous non-destructive monitoring of salt and water transfers throughout the manufacturing process. Recently, Fulladosa et al [121] and Santos-Garcés et al [122] [123] showed that water and salt contents, together with a w , could be estimated at different stages in the manufacture of dry-cured hams, from images obtained by X-ray tomography. Ultimately, by favoring the formation of the zinc-protoporphyrin complex responsible for the stable red color typical of Parma ham, the incorporation of nitrate/nitrite could also be discontinued in other types of dry-cured ham.…”
Section: Toward Dried-cured Pork Products With Higher Nutritional Valuementioning
confidence: 99%
“…The W hams were salted for 0.6, 0.7, 0.8, 1.1, 1.2, 1.3, 1.4 and 1.5 days/kg of green ham in order to obtain a wide variation of salt contents and followed a traditional drying process . When the drying process had finished, 27 commercial dry-cured hams from pigs consisting of at least 50% Iberian breed (IB, Iberian hams) characterized by a high fat content were selected at the end of the salting process according to their salt and fat contents, using computed tomography equipment (Santos-Garcés et al, 2012). All the hams, W and IB, were boned, trimmed of skin and external yellow subcutaneous fat and lean according to the common practices in industry, formatted in blocks of constant thickness (76.3 ± 3.5 mm) and divided into six portions (n = 276) for further X-ray analysis.…”
Section: Samplesmentioning
confidence: 99%